The Role of Life Skills in Attitude Towards Narcotic Drugs and Students' Self-Esteem - Mansoor Bagheri (Drug Control Headquarters, Research and Education Office, 2003)
The research seeks to examine the role of life skills concerning attitude towards narcotic drugs and students' self-esteem. The research design is experimental and includes pilot plans as well as pre-test and post-test control group designs. The sample groups include 60 male students (30 students in the pilot group an 30 students in the control group). The research results are as follows: 1.Offering life skills' training to students has caused meaningful variations (P-0.001level) in students' knowledge towards the issue of drugs. 2.Offering life skills' training to students has caused meaningful variations (P-0.001level) in students' attitude towards drugs 3.Offering life skills' training to students has caused meaningful variations (P-0.001level) in students' self-esteem